Diagnostic accuracy, operational feasibility, and cost considerations of Truenat MTB Plus and Xpert MTB/RIF Ultra for pulmonary tuberculosis - Zeeshan Sidiq; Ankita Anand; Kaushal Kumar Dwivedi; Payal Tyagi; Sanjay Rajpal; Kamal Kishore Chopra; Shikha Dhawan; Vishal Khanna (PLoS ONE, 2026)
Background Tuberculosis (TB) remains a major global health challenge, necessitating rapid and accurate diagnostic tools. The World Health Organization (WHO) endorses nucleic acid amplification tests (NAATs) like Truenat MTB Plus and Xpert MTB/RIF Ultra. While both are widely implemented, direct comparisons integrating diagnostic accuracy with operational and cost considerations across real-world settings are limited. This study aimed to compare the diagnostic accuracy of Truenat MTB Plus and Xpert MTB/RIF Ultra for the detection of Mycobacterium tuberculosis (MTB) and rifampicin resistance (RIF-R) among presumptive pulmonary TB patients in India, while also assessing their operational feasibility and cost-related parameters. Methods This prospective diagnostic accuracy study was conducted at New Delhi Tuberculosis Centre, in New Delhi, India, enrolling 664 presumptive pulmonary TB patients. Paired sputum specimens were tested using Truenat MTB Plus/MTB-RIF and Xpert MTB/RIF Ultra. Mycobacterial culture was used as the primary reference standard for MTB detection, and phenotypic drug susceptibility testing (pDST) was used for RIF-R detection. Sensitivity, specificity, and overall accuracy were calculated, and operational parameters, including invalid/indeterminate rates and cost per test, were recorded. Results The overall prevalence of culture-confirmed TB was 14.8% (98/664), with a RIF-R prevalence of 7.1% (7/98). Compared with culture, Xpert MTB/RIF Ultra demonstrated a sensitivity of 97.9% (95% CI: 95.2–100%) and a specificity of 95.5% (95% CI: 93.7–97.3%). Truenat MTB Plus showed a sensitivity of 92.5% (95% CI: 85.1–96.6%) and a specificity of 90.1% (95% CI: 86.8–92.6%). For RIF-R detection, Xpert Ultra had a sensitivity of 83.3% and a specificity of 100%, compared to Truenat MTB-RIF’s sensitivity of 75.0% and specificity of 100%. Operationally, Truenat had a significantly higher rate of invalid results (5.9% vs 0%) and RIF indeterminate results (46.5% vs 13.2%) compared to Xpert Ultra, resulting in an increased need for repeat testing. The cost per test was lower for Truenat (approximately INR 800 for MTB Plus) compared to Xpert MTB/RIF Ultra (approximately INR 1800). Conclusion Both Truenat MTB Plus and Xpert MTB/RIF Ultra demonstrated excellent diagnostic accuracy for TB detection. Xpert Ultra showed superior accuracy and lower indeterminate rates, while Truenat offers substantial operational and cost advantages for decentralized deployment; however, higher rates of invalid and indeterminate results may increase operational burden due to repeat testing. These findings support a tiered diagnostic approach, leveraging the strengths of both platforms to expand molecular testing access and accelerate progress toward global TB elimination goals.